2004
DOI: 10.1063/1.1792793
|View full text |Cite
|
Sign up to set email alerts
|

Strong luminescence from dislocation-free GaN nanopillars

Abstract: GaN nanostructures were prepared on Si(111) by a hot-wall epitaxy technique employing the modified two-step growth method. Isolated hexagonal pillar-like GaN nanostructures (GaN nanopillars) with the typical diameter, height, and density of 200–300nm, 0.5–1μm, and 3–4×108cm−2, respectively, are self-organized without intentional pre-processing to the Si substrate. The photoluminescence and cathodoluminescence (CL) measurements show the strong near-band-edge emissions without the yellow band at room temperature… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
31
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 10 publications
3
31
0
Order By: Relevance
“…Despite technological advances in group III-nitride device development, the effects of defects in these materials, mainly due to a lack of native GaN substrates, is an ongoing concern. Recently, however, many epitaxial nanostructures have been reported that are composed of relatively defect-free Ga x Al 1Àx N crystals with nanometer widths, and lengths on the order microns [1][2][3][4][5][6][7][8][9][10]. While these nanocolumns (NCs) take on a variety of aerial densities and the results span a range of growth parameters and epitaxial techniques, a key condition is that NC formation requires epitaxial growth under nitrogen-rich conditions-resulting in reduced Ga surface diffusion.…”
Section: Introductionmentioning
confidence: 99%
“…Despite technological advances in group III-nitride device development, the effects of defects in these materials, mainly due to a lack of native GaN substrates, is an ongoing concern. Recently, however, many epitaxial nanostructures have been reported that are composed of relatively defect-free Ga x Al 1Àx N crystals with nanometer widths, and lengths on the order microns [1][2][3][4][5][6][7][8][9][10]. While these nanocolumns (NCs) take on a variety of aerial densities and the results span a range of growth parameters and epitaxial techniques, a key condition is that NC formation requires epitaxial growth under nitrogen-rich conditions-resulting in reduced Ga surface diffusion.…”
Section: Introductionmentioning
confidence: 99%
“…Even when grown on mismatched substrates, the nanowire-substrate misfit strain can be accommodated coherently without nucleation of misfit dislocations. [8] Luminescence, normally quenched in the presence of optically active threading dislocations within GaN films, [9] is therefore comparatively strong in nanowires. [8] When other defects such as stacking faults are present, additional electronic states may be introduced near the band edges, and these can also influence the luminescence.…”
Section: Introductionmentioning
confidence: 99%
“…[8] Luminescence, normally quenched in the presence of optically active threading dislocations within GaN films, [9] is therefore comparatively strong in nanowires. [8] When other defects such as stacking faults are present, additional electronic states may be introduced near the band edges, and these can also influence the luminescence. [10] In order to investigate the implications of extended defects for nanowire-device applications, we imaged defects in GaN nanowires using high-resolution transmission electron microscopy (HRTEM) and cross-sectional transmission electron microscopy (XTEM).…”
Section: Introductionmentioning
confidence: 99%
“…Although the nitride-based optical devices have been widely spreading as usual light sources, there still remains difficulties in growth of nitride semiconductor with low dislocation density. In our previous work, we reported dislocation-free pillar-like GaN nanocrystals, "GaN nanopillars" [3]. The GaN nanopillars show excellent luminescence properties compared with typical GaN film.…”
mentioning
confidence: 98%